Dynamic in vitro gastric digestion of infant formulae made with goat milk and cow milk: Influence of protein composition. (October 2019) - Ye, Aiqian; Cui, Jian; Carpenter, Elizabeth; Prosser, Colin; Singh, Harjinder
Abstract: The gastric digestion behaviours of infant formulae made with goat milk and cow milk, with different ratios of casein to whey protein, were investigated using an in vitro dynamic infant human gastric simulator. The goat milk infant formulae formed smaller flocs of aggregated protein and oil droplets under gastric conditions, leading to faster protein digestion in goat milk infant formulae than in cow milk infant formulae. The extent of coagulation of protein and the size of flocculated oil droplets were dependent on the protein composition of the formulae. The casein-dominated cow milk infant formula had greater aggregation initially during gastric digestion, but a lower rate of casein digestion. The results suggest that the different composition of the casein micelles in goat milk may play an important role in the lower extent of coagulation and the faster protein gastric digestion in goat milk compared with cow milk.